Micro and macro analysis on the burden of COPD hospitalizations on the Bulgarian healthcare system. Issue 1 (1st January 2019) - Tachkov, Konstantin; Dimitrova, Maria; Mitov, Konstantin; Savova, Alexandra; Kamusheva, Maria; Dimitrov, Jordan; Manova, Manoela; Grekova, Daniela; Petkova, Valentina
Abstract: The aim of this study was to investigate the economic burden of Chronic Obstructive Pulmonary Disease (COPD)-related hospitalizations on a macro and micro level. Macro analysis was performed on the rate of DDD utilisation of COPD medicines, time of their inclusion in the reimbursement lists and the number of hospitalizations. On a micro level, a study of 426 patients with COPD was conducted to investigate the exacerbation and hospitalization rate relative to pharmacotherapy. A regression model, descriptive analysis, and Kruskal–Wallis non-parametric analysis were conducted. New drugs enter the market relatively quickly but are slow to be introduced into prescribing practices. The medicines' utilization in Bulgaria has increased from 20 to 21 million DDD for all therapeutic groups, especially for long-acting beta-agonists/long-acting muscarinic antagonists (LABA/LAMA) fixed-dose combinations. A marked increase in hospitalization rates was observed despite lower numbers of registered and monitored COPD patients nationally. However, the hospitalization rates due to exacerbations remained around 18–19%. Variation was observed in the number of hospitalizations for the studied period: increasing during the period 2013–2014 and decreasing over the following two years. This trend was also observed for the number of health insured COPD patients. The hospitalization costs increased from 5.2 to 5.7 million BGN. A statistically significant decrease in the number of hospitalizations for LAMA/LABA patients vs. LABA/inhaled corticosteroids (ICS) patients was observed. Overall, frequent hospitalizations increased the total cost of COPD therapy. Patients on new medicines with improved inhaler devices seem to suffer fewer hospitalizations.